Kinetic Study of Ammonium Desorption using Natural Zeolites from Cikalong - Abdusattar, Thareqa; Hadi, Abdul; Nuryoto, Nuryoto; Kurniawan, Teguh (World Chemical Engineering Journal, 2021)
Household liquid waste which contains ammonium is one of the major contributors to the wastewater effluent. The aim of investigation is to characterize and determine the adsorption capacity of natural zeolites from Cikalong for ammonium removal.  The effect of cations type, K+, Mg2+ and Ca2+, on ammonium desorptions was studied. Kinetic desorption study was also performed and fitted with various kinetic models. According to X-ray diffraction (XRD) pattern, the Cikalong natural zeolites were mordenite and clinoptilolite dominant type.  The morphology of the mordenite phase was appeared as needles shape. The ratio of Si to Al was 6.86 according to X-ray fluorescence (XRF). The surface area was 187 m2/g which was determined by Brunauer–Emmett–Teller (BET) model. Desorption using K+ solution showed the shortest time and the highest rate for ammonium desorption. The calculation using nonlinear method was carried out to optimize the desorption kinetic parameters. The pseudo 1st order desorption kinetics model showed the smallest error with sum of squared error (SSE) 0.00209.